SISTEM PENANGKAL PETIR PADA GEDUNG KEMANG GALLERY MEDAN - Saragih, Berlin; Siburian, Jhonson M.; Purba, Jaya Lukita (JURNAL TEKNOLOGI ENERGI UDA: JURNAL TEKNIK ELEKTRO; Vol 9 No 1 (2020): MARET, 2020)
Lightning is a process of events in the atmosphere in the form of the discharge of electric charge from charged clouds. When releasing this charge towards an object, we call it a bolt of lightning. Given the possibility of damage due to lightning strikes that are quite dangerous, then there are efforts to overcome the dangers of lightning strikes. One of them is with lightning rod electrodes or also called "lightning conductor". This protection system is needed considering the Kemang gallery building is quite high among the buildings in the vicinity and is in locations with high thunder day levels around 170 thunder days each year. By using the protection chamber concept according to the electro geometric model, the distance of the protection chamber from the lightning rod used and the level of protection needed will be calculated and determined. The calculation results show that the lightning rod mounted above the Kemang gallery building is sufficient to protect the entire area around the Kemang gallery building.